Adult day services and dementia caregivers' daily affect: the role of distress response to behavioral and psychological symptoms of dementia. (2nd January 2021) - Bangerter, Lauren R.; Liu, Yin; Kim, Kyungmin; Zarit, Steven H.
Abstract: Adult day services (ADS) provide respite for dementia caregivers and directly reduce exposure to behavioral and psychological symptoms of dementia (BPSD). This study examines the psycho-behavioral mechanism on how daily ADS use may benefit caregivers' daily affect through its impact on the distress associated with BPSD stressor exposure. The sample consists of dementia caregivers ( N = 173) who participated in an ADS intervention across 8 days. Multilevel structural equation modeling was conducted to examine the within- and between-person mediating effects of BPSD distress on the direct associations between daily ADS use and daily negative and positive affect. ADS days were associated with lower daily negative affect and higher daily positive affect; the significant within-person effect of ADS use on daily affect was mediated by daily BPSD distress. Findings highlight the association between daily ADS use and caregiver affective well-being. This understanding is important for designing respite and other interventions to help dementia caregivers manage the daily stress of caregiving.